Development of Science Literacy Corner in WiSe Reading Community: Bringing Science to Everyone - Fidia Fibriana; Rizki Nor Amelia; Lutfia Nur Hadiyanti; Hendra Febriyanto; M Ahganiya Naufal; Ni Luh Tirtasari; Aya Sofia; Surtini Hadi (Jurnal Abdimas, 2024)
The Wiji Semi (WiSe) Reading Community, in collaboration with Universitas Negeri Semarang, initiated a Science Literacy Corner (Pojok Literasi Sains) to enhance the scientific literacy of its volunteers to broaden the knowledge of how science to WiSe visitors, especially children. This initiative aimed to improve volunteers' abilities in explaining scientific phenomena, evaluating and designing scientific explorations, and interpreting data scientifically. The program included online lectures, mentoring sessions, and hands-on practicums. Pretest and posttest evaluations indicated notable improvements in the volunteers' skills, particularly in explaining scientific phenomena (73% to 79%) and interpreting data scientifically (82% to 86%) while maintaining a high level of competence in evaluating and designing scientific exploration (83%). Overall, the program effectively empowered volunteers to better communicate scientific concepts, thus fostering a greater understanding and engagement with science within the community.